Construction of an Implant‐Retained Auricular Prosthesis with the Aid of Contemporary Digital Technologies: A Clinical Report. Issue 2 (4th September 2012) - Hatamleh, Muhanad M.; Watson, Jason
Abstract Implant‐retained auricular prostheses are a successful treatment modality for children with microtia. They involve only minor surgical intervention of implant placement and result in an esthetically pleasing outcome. Integration of digital technologies (DT) in the prosthetic reconstruction process is a new approach toward enhancing outcomes. In this report we present a case of auricular prosthetic reconstruction following two implant placements in the right mastoid region. The ear prosthesis was constructed with the aid of various DTs. A structured light laser scanner was used to digitize the nondefect patient ear. The digitized 3D ear was then manipulated in specialist software, mirrored to reflect the opposing side, and a Rapid Prototyping (RP) machine (Z‐Corp) was used to manufacture the soft tissue required. This RP‐mirrored ear model allows very accurate reproduction to replicate missing soft tissue. A color Spectrometer was used to accurately reproduce skin tones. The use of these technologies is now routine practice at our unit. They enhance prosthetic outcomes and esthetics, save the prosthetist's time, and are digitally stored and subsequently readily available and reproducible.